Pekande- Kandea Tradition In Sangia Wambulu, Southeast Sulawesi (A Cultural Study) - Emma Bazergan; Lusy Anggreani; Rabi'al Adawiah (Tamaddun Life, 2016)
The aims of this research were to find out about the process of Pekande – Kandea tradition and values moral are in Pekande - Kandea tradition in Buton history. This research used qualitative descriptive that could give an explanation about the process and moral values moral about Pekande – Kandea tradition. The result of this research should that the process of Pekande – Kandea has uniqueness and moral values moral that have a connection with heroism and togetherness. And this tradition one and only that exist also still running every year in Buton Island. The conclusion of this research is Pekande - kandea is a cultural heritage that is a nation that contains a variety of ideas knowledge of customs and behavior of the community in the past. Pekande – Kande tradition happened two times but in a different eras. This tradition also has a relationship with the Tolandona knight’s struggle who wants to return sovereignty Sultanate of Buton.